Cerebrospinal fluid cholinesterase activity in children with meningitis - Aldeen Alnoori; Mohammed Khalid Jamal (University of Mosul, 2011)
Objective: To assess the changes of cerebrospinal fluid (CSF) acetyl cholinesterase (AChE) activity in children with acute bacterial meningitis in comparison to healthy age and sex matched controls. Patients and methods: Out of 41 cases admitted to Alkhansaa pediatric and dilivery hospital (Mosul city) between January 2010 and July 2010, 28 cases proved to be a case of Haemophilus influenzae meningitis, 13 child proved lack from any type of meningitis with age and sex matched subjects taken as a control group. Initially from all of the studied children (patients and controls) about 5 ml CSF samples were taken and assayed for appearance, leucocytes, red blood cells, sugar, protein and AChE activities by spectrophotometric method. Results: There were a significant increase in CSF WBCs count, RBCs count, protein levels, AChE activity with a decrease in CSF glucose level for children with acute bacterial meningitis in comparison to the control group. Conclusion: There is an important value for measurement of CSF AChE activity for confidential diagnosis of children with acute bacterial meningitis specially for those with equivocal decision by using the traditional parameters.